Alexander Holden: capstone - Holden, Alexander, artist (Colorado State University. Libraries, 2026)
The artist's statement: Blind exploration is how I would describe my creation process. Most of my pieces are created without any plan, without any idea of what the final piece might look like. This allows me to shape and form my pieces as they develop, making cuts or changes without worrying about how it affects the outcome. My best pieces are the results of what I call digital play, messing around in software and space without any rhyme or reason, not expecting a specific outcome. While the medium in which I work shifts between projects, my primary method for creation is digital video and digital 3D. In this space, I'm able to create entire worlds in which I have total control over every parameter, from organization of space to the way physics interacts with the environment. This allows for what I consider to be the best form of digital play.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art